Catalyzing Remote Collaboration During the COVID-19 Pandemic and Beyond: Early Career Oceanographers Adopt Hybrid Open Science Framework - Rudzin, Johna E.; Soule, Dax C.; Whitaker, Justine; Berger, Halle; Clayton, Sophie; Fogaren, Kristen E. (Frontiers in Marine Science, 2022)
The COVID-19 pandemic introduced many challenges for research scientists: reduction of lab and field observation collection and in-person meetings. These new constraints forced researchers to remote work and virtual networking, dramatically influencing scientific inquiry. Such challenges are compounded for those in early stages of their career, where data collection and networking are vital to be seen as productive. However, during this time of remote work, we, a collective of early-career oceanographers, were actively developing and improving on an already-existent hybrid community of practice. Through our experiences, we believe this type of framework can enhance virtual collaboration to the point that it outlasts the pandemic and helps create new synergies that will diversify and enhance scientific inquiry within the ocean science community. We describe a hybrid community of practice and an example workflow that models effective collaboration. We have found that three components to this model are necessary for effective collaboration, inspiration, and communication: 1) openly accessible data, 2) software, computational, and professional-development resources, and 3) a team science approach. In our experience, both the in-person and remote aspects of the model are important. In person collaboration is key to expanding the community of practice and invigorating those already within the community. Remote collaboration has been critical for effective collaborations between in-person activities and has proven to maximize outputs during in-person collaborations. While the three components of this model are not new to the scientific community, we believe that utilizing them strategically post-pandemic will diversify and expand scientific collaboration in oceanography.